1989
DOI: 10.1177/036354658901700605
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of chronic Achilles tendinitis

Abstract: Between 1977 and 1985, 170 patients suffering from chronic Achilles tendinitis were treated surgically. Ninety-one patients with 143 tendons returned for followup. The duration of preoperative symptoms averaged 18 months. In all cases, conservative treatment was first attempted but failed to alleviate symptoms. Only those patients whose lesions and symptoms were confined to the Achilles tendon segment 2 to 6 cm proximal of the insertion were included in this study. All athletes who had an insertion tendinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(138 citation statements)
references
References 10 publications
4
130
0
4
Order By: Relevance
“…When studying Achilles tendon injuries in athletes, Kvist (1991) found that the mean age of subjects with Achilles tendon disorders was 28±9 years, while it was 20±8 years in those without these disorders. Treatment studies (both surgical and non-surgical), that not only include athletes, report that the average age of patients with Achilles tendinopathy ranges between 30 and 55 years, with a total range from 17-80 years of age (Nelen et al, 1989, Leach et al, 1992, NiesenVertommen et al, 1992, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Neeter et al, 2003, Alfredson and Öhberg, 2005d. In a prospective study, Johansson (1986) reported that the annual incidence of Achilles tendon overuse injury in elite orienteers was 7%.…”
Section: In a Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…When studying Achilles tendon injuries in athletes, Kvist (1991) found that the mean age of subjects with Achilles tendon disorders was 28±9 years, while it was 20±8 years in those without these disorders. Treatment studies (both surgical and non-surgical), that not only include athletes, report that the average age of patients with Achilles tendinopathy ranges between 30 and 55 years, with a total range from 17-80 years of age (Nelen et al, 1989, Leach et al, 1992, NiesenVertommen et al, 1992, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Neeter et al, 2003, Alfredson and Öhberg, 2005d. In a prospective study, Johansson (1986) reported that the annual incidence of Achilles tendon overuse injury in elite orienteers was 7%.…”
Section: In a Populationmentioning
confidence: 99%
“…One study reports that 89% of the runners with Achilles tendinopathy were men (Kvist, 1991). In a review of several treatment studies, the percentage of men was between 45-86%, with the lower percentages seen in the more recent studies (Nelen et al, 1989, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Alfredson and Öhberg, 2005d.…”
Section: In a Populationmentioning
confidence: 99%
See 3 more Smart Citations